The Determinant of The Working Poor’s Income in The South-West Areas of Aceh 2010 and 2020 - T Zulham; Yayuk Eko Wahyuningsih; Tasdik Ilhamudin; Rollis Juliansyah (Proceedings of AICS - Social Sciences, 2021)
Poverty is a complex and multidimensional problem that is influenced by various interrelated factors, including: income level, education, access to goods and services, geographical location, gender and environmental conditions. Overall poverty rates have declined in all regions over the last 10 years. However, if we look at the poverty rate in the South-West (Barsela) region of Aceh, it is higher than the provincial and Indonesian averages. This indicates that there are many people living below the poverty line in the Barsela area. The phenomenon of working poor above certainly raises the question that there are things which are the determining factors why the welfare or income of workers is still very low. This study aims to analyze the income determinants of the working poor in the South-West Aceh region in 2010 and 2020. These determinants include socio-demographic variables, namely gender, area of residence, marital status, age, education level, business field, employment sector, and number of hours worked. The data used is secondary data and taken from Central Bureau of Statistics of Aceh. This study uses comparative descriptive qualitative analysis with sample of Susenas 2010 is 15.830 persons and the number of workers 3.589 persons. In addition, sample of Susenas 2020 is 17.197 persons with the number of workers 7.013 persons. On the other hand, women experienced a decline. Thus, this data remains unchanged in that the latest data in 2019 shows that the number of workers is also still dominated by South Aceh Regency at 98,000 people and the lowest is Subulussalam City at 29,000 people. Based on this data, it is suggested to the district/city governments in the Barsela region to improve the welfare of the working poor through the provision of allowances to the poor, so that they are able to get out of the poverty trap.Keywords: determinant, working poor and Barsela region.